Getting things done : how to achieve stress-free productivity - Allen, David, 1945 December 28- (London : Piatkus, 2008)
Is your workload overwhelming? Does it just keep mounting up while your stress levels reach fever pitch? In Getting Things Done David Allen teaches you how to keep a clear head, relax and organise your thoughts while implementing the methods that he has introduced at organisations like Microsoft, Lockheed and the US Department of Justice: Learn the 'do it, delegate it, defer it, drop it' principle to empty your in-tray. Handle e-mail, paperwork and unexpected demands in a system of self-management. Plan and progress projects. Reasses goals and stay focused. Apply the two minute rule when deciding what to do now and what to defer. Overcome feelings of anxiety and being overwhelmed. With clear and specific methods and advice, David Allen's tried and trusted formula for business efficiency could transform the way you operate and your experience of work.
Includes index.
Keywords: Time management; Self-management (Psychology)